A systematic review of interventions for promoting active transportation to school - Evenson Kelly R; Chillón Palma; Vaughn Amber; Ward Dianne S (BMC, 2011)
Abstract Background Active transportation to school is an important contributor to the total physical activity of children and adolescents. However, active school travel has declined over time, and interventions are needed to reverse this trend. The purpose of this paper is to review intervention studies related to active school transportation to guide future intervention research. Methods A systematic review was conducted to identify intervention studies of active transportation to school published in the scientific literature through January 2010. Five electronic databases and a manual search were conducted. Detailed information was extracted, including a quantitative assessment comparing the effect sizes, and a qualitative assessment using an established evaluation tool. Results We identified 14 interventions that focused on active transportation to school. These interventions mainly focused on primary school children in the United States, Australia, and the United Kingdom. Almost all the interventions used quasi-experimental designs (10/14), and most of the interventions reported a small effect size on active transportation (6/14). Conclusion More research with higher quality study designs and measures should be conducted to further evaluate interventions and to determine the most successful strategies for increasing active transportation to school.